Targeted modulation of MMP9 and GRP78 via molecular interaction and in silico profiling of Curcuma caesia rhizome metabolites: A computational drug discovery approach for cancer therapy - Mahek Desai; Soham Bhattacharya; Saurabhkumar Mehta; Kaushiki Joshi; Mitesh B. Solanki; Trilok Akhani; Iva Viehmannová; Eloy Fernández Cusimamani (PLoS ONE, 2025)
Cancer remains a leading cause of mortality worldwide, with conventional therapies showing limited efficacy and high toxicity. The increasing incidence and therapeutic resistance necessitate alternative strategies. In this regard, phytochemicals have emerged as potential sources of developing safer and novel anti-cancer agents. This study employs a structure-based drug design approach, integrating molecular docking, molecular dynamics (MD) simulations, and in silico profiling, to investigate the anti-cancer potential of metabolites from Curcuma caesia rhizomes. The research targets key cancer-associated proteins, Matrix Metalloproteinase-9 (MMP9) and Glucose-Regulated Protein 78 (GRP78), identified through expression analysis, functional network mapping, and pathway enrichment as critical mediators of cancer progression and metastasis. A comprehensive molecular docking analysis of 101 bioactive compounds from C. caesia rhizomes identified curcumin and bis-demethoxycurcumin as promising candidates, demonstrating high binding affinities and stable interactions with MMP9 and GRP78. MD simulations further validated the stability and robustness of these interactions under dynamic physiological conditions. Pharmacological profiling, including ADMET analysis, Lipinski’s rule compliance, and bioactivity scoring, revealed favorable drug-like properties for both compounds, including strong absorption, distribution, low toxicity, and potential therapeutic activities such as enzyme inhibition and nuclear receptor-mediated processes. KEGG pathway enrichment analysis confirmed their involvement in key biological pathways linked to cancer progression, underscoring their therapeutic potential. The findings highlight curcumin and bis-demethoxycurcumin as promising phytochemical candidates for cancer therapy, capable of modulating MMP9 and GRP78 to suppress tumor progression. While these results provide a solid basis for their therapeutic potential, further experimental studies and clinical trials are crucial to confirm their efficacy and safety for human applications.